Planting the seeds of change: Directionality in the narrative construction of recovery from addiction. Issue 6 (3rd June 2017) - Kougiali, Zetta G.; Fasulo, Alessandra; Needs, Adrian; Van Laar, Darren
Abstract : Objective: The dominant theoretical perspective that guides treatment evaluations in addiction assumes linearity in the relationship between treatment and outcomes, viewing behaviour change as a 'before and after event'. In this study we aim to examine how the direction of the trajectory of the process from addiction to recovery is constructed in personal narratives of active and recovering users. Design: 21 life stories from individuals at different stages of recovery and active use were collected and analysed following the principles of narrative analysis. Results: Personal trajectories were constructed in discontinuous, non-linear and long lasting patterns of repeated, and interchangeable, episodes of relapse and abstinence. Relapse appeared to be described as an integral part of a learning process through which knowledge leading to recovery was gradually obtained. Conclusion: The findings show that long-term recovery is represented as being preceded by periods of discontinuity before change is stabilised. Such periods are presented to be lasting longer than most short-term pre-post intervention designs can capture and suggest the need to rethink how change is defined and measured.